GAMBARAN PENGETAHUAN IBU TENTANG KONTRASEPSI TUBEKTOMI DI KLINIK HARAPAN IBU TAHUN 2015 - TISNILAWATI . (LP2MTBM MAKARIOZ, 2018)
Indonesia's population is a population problem in Indonesia. The Indonesian population is 782,682 who are KB participants. According to the 2013 BKKBN data (7.64%), 98,594 Implant participants (12.60%), 358,470 injection participants (45.80%), 203,878 Pilots participants (26.05%), 13,623 MOW participants (1.74% ), 2,589 MOP participants (0.33%) and condom participants 45,753 (5.85%). The purpose of the study is to find out the definition characteristics, advantages, weaknesses, indications, and contraindications in the Maternal Hope Maternity Clinic 2015.Descriptive research to find out the description of maternal knowledge about tubectomy contraception with the population is all mothers who came to visit Harapan Ibu Maternity Clinic in 2015 from July 3 to July 5 as many as 30 respondents. The sampling technique in this study is arcidental that is 30 respondents using a questionnaire. Analysis is discussed in accordance with existing theories and libraries.From the results of the researchers who used 30 majority respondents poor knowledge of 15 respondents (50%), and a minority of well-informed as many as 13 respondents (43.3%). Based on age, the majority of respondents were quite knowledgeable as many as 27 respondents (90%) in the age group of 20-35 years. And the minority is poor knowledge of 1 respondent (3.3%) in the age group <20 years. Based on education, the majority were knowledgeable enough as many as 15 respondents (50%) in the high school education group, and the minority had less knowledge as much as 1 respondent (3.3%) in the elementary education group. Based on the information sources, the majority of them were knowledgeable as many as 20 respondents (66.6%) and the minority had poor knowledge as many as 18 respondents (6.6%).Based on the results of the study it can be concluded that the mothers who visited the Harapan Ibu Maternity Clinic had poor knowledge about tubectomy contraception and there were still many mothers who had not used tubectomy contraception. Therefore, it is expected that all mothers who visit the Harapan Ibu Maternity Clinic can understand and use tubectomy contraception.